2011
DOI: 10.1038/nature10233
|View full text |Cite
|
Sign up to set email alerts
|

Earth’s Trojan asteroid

Abstract: It was realized in 1772 that small bodies can stably share the same orbit as a planet if they remain near 'triangular points' 60° ahead of or behind it in the orbit. Such 'Trojan asteroids' have been found co-orbiting with Jupiter, Mars and Neptune. They have not hitherto been found associated with Earth, where the viewing geometry poses difficulties for their detection, although other kinds of co-orbital asteroid (horseshoe orbiters and quasi-satellites) have been observed. Here we report an archival search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
146
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 18 publications
4
146
1
3
Order By: Relevance
“…Infrared measurements from NEOWISE have provided preliminary estimates of diameters and albedos . 2010 TK 7 is thought to be temporarily captured by Earth, with a dynamical stability timescale of ∼7000 years (Connors et al 2011;Marzari & Scholl 2013). By contrast, 2010 SO 16 librates across the L3 Earth-Sun Lagrange point in a horseshoe pattern that has the longest known stability of any Earth co-orbital, several hundred thousand years (Christou & Asher 2011).…”
Section: Earth Co-orbitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared measurements from NEOWISE have provided preliminary estimates of diameters and albedos . 2010 TK 7 is thought to be temporarily captured by Earth, with a dynamical stability timescale of ∼7000 years (Connors et al 2011;Marzari & Scholl 2013). By contrast, 2010 SO 16 librates across the L3 Earth-Sun Lagrange point in a horseshoe pattern that has the longest known stability of any Earth co-orbital, several hundred thousand years (Christou & Asher 2011).…”
Section: Earth Co-orbitalsmentioning
confidence: 99%
“…Among the near-Earth objects discovered by NEOWISE during its post-cryogenic mission is the first known Earth Trojan, 2010 TK 7 and an object in a so-called "horseshoe" orbit co-orbital with Earth, 2010 SO 16 (Connors et al 2011;Christou & Asher 2011;Mainzer et al 2012a). 2010 TK 7 was discovered by NEOWISE because its ∼395-year libration period caused it to move to the region near 90…”
Section: Earth Co-orbitalsmentioning
confidence: 99%
“…Any primordial Saturn and Uranus Trojans would have been subsequently lost through planetary perturbations (Nesvorný and Dones, 2002;Dvorak et al, 2010;Hou et al, 2014), with the known Uranus Trojans thought to be temporarily captured from among the Centaurs (Alexandersen et al, 2013;de la Fuente Marcos and de la Fuente Marcos, 2014). Some hypothetical Trojans of Earth would have been long-term stable, with the situation at Venus being less clear (Tabachnik and Evans, 2000;Cuk et al, 2012;Marzari and Scholl, 2013); however, so far only temporary coorbitals of these planets are known (Christou, 2000;Christou and Asher, 2011;Connors et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial planets may support a population of Trojan asteroids, (e.g. the Earth Trojan 2010 TK 7 discovered by Connors et al 2011), but so far no stable population has been identified.…”
Section: Introductionmentioning
confidence: 99%